The Correlation between Content Schemata, Linguistic Schemata and Reading Comprehension of Foreign Language Learners - Roziqin, Zainul; Zuhairi, Alfan; Mistar, Junaidi (STAI Miftahul Ula Nganjuk, 2023)
Reading is a complicated process that involves the reader's engagement with the text to develop meaning. Language proficiency is regarded to be more significant and to contribute more to reading comprehension in reading a second language or a foreign language than other aspects. This study is aimed at to measure which of the content schemata and linguistic schemata contributes the most to reading comprehension. The study was carried out in a sample of 35 English students of the first semester at Foreign Language Class in Al-Qolam Islamic Institute Gondanglegi Malang. The data collection involved two instruments, namely self-assessment, linguistic test and reading comprehension test. To achieve the purpose of the present study, the data were analyzed by using simple correlation with the help of SPSS 16. The result of the computation of simple correlation showed that linguistic schemata contribute more to reading comprehension. The effect analysis of the combined predictors and reading comprehension indicating significance at .000. Simple regression correlation calculations required a significance level of less than 0.05. In other words, there was a correlation between content schemata, linguistic schemata and reading comprehension. EFL teaching professionals and other scholars who intend to study relevant subjects in future research are addressed in suggestions made based on the results.